Os requisitos cumulativos na judicialização da saúde: uma análise da jurisprudência à luz dos direitos fundamentais e da responsabilidade fiscal - Parrião, Luiz Fernando Moreira Aguiar (Universidade Federal do Tocantins, 2021)
The study aims to promote a reflection on the judicialization of health. Identify restrictive provisions on the granting of medicines through an analysis of the jurisprudence of the superior courts in Brazil. Understand the possibility of reconciling different interests – the protection of fundamental rights and the commitment to fiscal responsibility. Specifically, analyze the impact of drug granting and the observance of fundamental rights in drug granting judgments. The work uses the hypothetical-deductive method and is based on bibliographical research selected from publications related to the area of judicialization of health, economics, fiscal responsibility, fundamental and constitutional rights.